Flood risk management governance and resilience: A systematic literature review / Asiyah Kassim and Katherine Daniell - Kassim, Asiyah; Daniell, Katherine (2021)
Resilience is key to managing complex social-ecological systems and reducing vulnerability to uncertainty and complexity of unexpected change. Flood is one of the most wicked and complex ecological and environmental problems. Yet, flood risk management (FRM) has emerged mainly from a culture of resistance. Research on how 'good governance' can promote resilience to flooding has increased significantly over the past few decades. Thus, practical guidance for improving FRM in enhancing resilience to floods should be available from current research. However, there is a lack of investigation of the state of FRM adaptation and resilience research as it relates to governance, nor of the key gaps in knowledge that need to be addressed to improve resilience to flooding. This paper examines current academic conversations and trends on how flood management relates to flood resilience. The inquiry is based on the argument that understanding how the scholarly community relates resilience in FRM research to governance, policy, and actions will help in identifying and prioritizing research needs that enable FRM policy and process enhancements. This is done by examining how the scholarly, peer-reviewed journal literature has attempted the subject of FRM governance and resilience to flooding, the dominant lines of inquiry, and the gaps in knowledge and understanding.